The marketing analysis of the market of medicines for the treatment of the wound process and burn disease at the hospital stage in the military personnel: uk. - Tarasenko, V. O.; Shmatenko, O. P.; Syrota, P.S.; Myropolska, O.V.; Shmatenko, V.V. (Social Pharmacy in Health Care, 2021)
Aim. To summarize the list of medicines that can be used at various stages of the treatment of burn disease and wound healing at the hospital stage in the military personnel; conduct the marketing analysis of the Ukrainian market of these medicines in order to determine the feasibility of creating an ointment for the treatment of inflammatory skin diseases and burns. Materials and methods. The study objects were the “State Register of Medicinal Products of Ukraine” information and search system and the Compendium. When conducting our studies the following scientific and system-review methods of the information search were used: bibliographic, documentary, content analysis, comparison method, system analysis, marketing research. Results. As a result of the study of the range of drugs for wound healing presented at the pharmaceutical market of Ukraine, it has been found that 64 % are drugs of the Ukrainian production, foreign drugs are 36 %. The distribution of soft drug forms registered in Ukraine has been carried out by pharmacological groups; it has been found that the percentage of antimicrobial and antifungal drugs is almost the same (15.8 % and 15.2 %, respectively). Steroidal anti-inflammatory drugs predominate over nonsteroidal ones (14.9 % and 11.4 %, respectively). The studies conducted have shown that at the domestic market there are many drugs of foreign production, which have no Ukrainian analogs. The marketing research has shown that combined drugs are more effective for the treatment of burns. They act simultaneously in several directions and facilitate the healing process. Among the drugs considered combined medicines occupy 42 %, while the share of monocomponent drugs is 58 %. The amount of synthetic drugs is 88 % and significantly exceeds the number of herbal medicines (12 %). Conclusions. The concept and methodology for the treatment of burns are summarized. It has been determined that the drugs of choice are complex soft drug forms. As a result of the marketing research on the structure and nomenclature of soft drug forms it has been found that at the domestic pharmaceutical market soft drug forms of foreign production is 36 %, and domestic ones – 64 %. It has been determined that the number of drugs for local wound healing is about 6 % of the total range of soft drug forms and presented mainly by monocomponent drugs (58 %). The analysis of the range of drugs with the anti-burn and antiseptic action by dosage forms has shown that ointments are the largest share – 67%, drugs in the form of creams – 18%. Key words: marketing analysis; servicemen; burn disease; wound process; hospital stage of treatment.